Mycelium-bound lipase from a locally isolated strain of Geotrichum candidum - Loo, Joo Ling; Khoramnia, Anahita; Lai, Oi Ming; Long, Kamariah; Mohd Ghazali, Hasanah (MDPI, 2014)
Mycelium-bound lipase (MBL), from a locally isolated Geotrichum candidum strain, was produced and characterized as a natural immobilized lipase. A time course study of its lipolytic activity in 1 L liquid broth revealed the maximum MBL activity at 4 h for mycelium cells harvested after 54 h. The yield and specific activity of MBL were 3.87 g/L dry weight and 508.33 U/g protein, respectively, while less than 0.2 U/mL lipase activity was detected in the culture supernatant. Prolonged incubation caused release of the bound lipase into the growth medium. The growth pattern of G. candidum, and production and properties of MBL were not affected by the scale. The stability of mycelia harboring lipase (MBL), harvested and lyophilized after 54 h, studied at 4 °C depicted a loss of 4.3% and 30% in MBL activity after 1 and 8 months, while the activity of free lipase was totally lost after 14 days of storage. The MBL from G. candidum displayed high substrate selectivity for unsaturated fatty acids containing a cis-9 double bond, even in crude form. This unique specificity of MBL could be a direct, simple and inexpensive way in the fats and oil industry for the selective hydrolysis or transesterification of cis-9 fatty acid residues in natural triacylglycerols.